Effect of Cyclosporine-A on Paraoxonase Activity in - H. Argani (International Journal of Organ Transplantation Medicine, 2011)
Background: Many adverse effects have been reported on using cyclosporine (CSA) in organ transplantation.Objective: To investigate the effects of CSA on paraoxonase (PON) activity and lipid peroxidation metabolitesin early and late-stage of peroxidation and also total antioxidant (TA).Methods: Twenty 220-250 g adult male Wistar rats were included in the study. The animals were storedfor one week in the animal room before the initial injection to habituate with temperature, humidity, andcircadian rhythm of day (12 h) and night (12 h). The temperature was kept at 23 °C. Animals had accessto food and water ad libitum.Results: A significant (p=0.002) increase in the serum levels of conjugated diones was observed in the casecompared to the control group. At the end of the study, malondialdehyde (MDA) levels in CSA group wassignificantly (p=0.01) higher than the control group. Serum PON1 activity was significantly (p=0.004)lower in the case than the control group.Conclusion: CSA administration could impair oxidant-antioxidant pathways and increase oxidative stress.Antioxidant therapy could be beneficial in patients treated with CSA.